Implementasi Pembelajaran Berdiferensiasi untuk Meningkatkan Kreativitas Anak - Naili Sa'ida (Institut Agama Islam Negeri Madura, 2023)
This study aims to describe differentiation learning in increasing children's creativity. The research approach used is a qualitative research approach. Data was collected using observation sheets, interviews and documentation. The documentation used is anecdotal notes, child development reports and works. The data that has been collected is analyzed using the Miles and Huberman data analysis technique which contains four stages including: data collection, data reduction, data display, and drawing conclusions. To see the validity of the data in this study, the validity of the data was tested using technical triangulation. The results of the study show that differentiated learning develops children's creative abilities through providing opportunities for children to learn according to their individual characteristics and providing various choices of media that can be used by children according to their interests. So that children are free to be creative through facilitated media